Using folktales - Taylor, Eric K. (Eric Kenneth) (New York : Cambridge University Press, 2000)
Explains how educators can use the unique characteristics of folktales to promote language learning, with practical ideas for using folktales in the classroom to generate listening and reading texts, develop critical thinking skills, stimulate discussion, address grammar, and build academic skills.
Includes bibliographical references (p. 277-286) and indexes.
Professional
Keywords: English language -- Study and teaching -- Foreign speakers; Language arts (Elementary); Tales -- Study and teaching; Tales -- Study and teaching -- Activity programs; English as a second language; Folklore -- Study and teaching; Language arts